ANALISIS KUALITAS INSTRUMEN ASESMEN RANAH KOGNITIF PENDIDIKAN AGAMA ISLAM DI UNIVERSITAS NEGERI YOGYAKARTA - Jihanna Amalia (Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2023)
Abstract Educators need to pay attention to the extent to which the reasons underlying the quality of the assessment instrument. Assessment of student learning outcomes includes competence attitudes knowledge and skills. In this study focused on analyzing the quality of cognitive domain assessment instrument for Islamic religious education lectures with qualitative analysis technique. The research embodies a variety of literature research. Methods of data accumulation, namely the documentation section and independent review with the descriptive analysis method. The data source is in the form of secondary data from several books and journals. The results of qualitative analysis of the quality of the cognitive doamain assessment instruments in the form of multiple choice and descriptions show that: 1) the material domain is sufficient in accordance with the indicators, measurement objectivies, and level of education. However, there are still several modules that do not cover indicators comprehensively; 2) the realm of construction is clearly arranged, avoiding alternative answers, the items are not related to each other, and do not have multiple meanings; 3) the realm of communicative language, according to an enhanced spelling order, and does not contain language that offends students. Keywords: Quality Instrumen Asessment, Cognitive, Islamic Religious Education Abstrak Pendidik perlu memperhatikan sejauhmana alasan yang mendasari kualitas instrumen penilaian. Penilaian hasil belajar peserta didik mencakup kompetensi sikap, pengetahuan, dan keterampilan. Pada penelitian ini terfokus untuk menganalisis kualitas instrumen penilaian ranah kognitif mata kuliah pendidikan agama Islam dengan teknik analisis kualitatif. Penelitian mewujudkan ragam penelitian kepustakaan. Metode akumulasi data yaitu kajian dokumentasi. Dengan metode Analisis Isi-deskripsi. Sumber data berupa data sekunder yang bersumber dari berbagai buku, dan jurnal. Hasil analisis kualitatif kualitas instrumen asesmen ranah kognitif dalam bentuk multiple choice maupun uraian menunjukkan bahwa: 1) ranah materi sudah cukup sesuai dengan indikator, tujuan pengukuran, dan jenjang pendidikan. Namun masih terdapat beberapa modul yang belum komprehensif mencakup indikator; 2) ranah konstruksi disusun secara jelas, menghindari adanya alternatif jawaban, butir soal tidak saling berkaitan, dan tidak bermakna ganda; 3) ranah bahasa komunikatif, sesuai tatanan ejaan yang disempurnakan, dan tidak mengandung bahasa yang menyinggung peserta didik. Kata kunci : Kualitas Instrumen Penilaian, Kognitif, Pendidikan Agama Islam